2019
DOI: 10.3390/polym11091461
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photovoltaic Effect of Electron-Withdrawing Units for Low Band Gap Conjugated Polymers Bearing Bi(thienylenevinylene) Side Chains

Abstract: A novel (E)-5-(2-(5-alkylthiothiophen-2-yl)vinyl)thien-2-yl (TVT)-comprising benzo[1,2-b:4,5-b’]dithiophene (BDT) derivative (BDT-TVT) was designed and synthetized to compose two donor-acceptor (D-A) typed copolymers (PBDT-TVT-ID and PBDT-TVT-DTNT) with the electron-withdrawing unit isoindigo (ID) and naphtho[1,2-c:5,6-c′]bis[1,2,5]thiadiazole (NT), respectively. PBDT-TVT-ID and PBDT-TVT-DTNT showed good thermal stability (360 °C), an absorption spectrum from 300 nm to 760 nm and a relatively low lying energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The incorporation of the two-dimensional conjugated side-chain to the polymer backbone was confirmed to improve the electrical conductivity of conjugated polymers [ 31 , 32 , 33 ], thus was widely used as the active layers in the organic-field effect transistors (OFETs) and organic solar cells (OSCs) [ 34 , 35 ]. Recently, we attempted to investigate the thermoelectric performance of BDT-based polymers with two-dimensional conjugated side-chains [ 36 ] and obtained good thermoelectric power factor of 101.3 μWm −1 K −2 , which is almost 100 times larger than that of the BDT–EDOT copolymers with one dimensional aliphatic side chain (0.9 μWm −1 K −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the two-dimensional conjugated side-chain to the polymer backbone was confirmed to improve the electrical conductivity of conjugated polymers [ 31 , 32 , 33 ], thus was widely used as the active layers in the organic-field effect transistors (OFETs) and organic solar cells (OSCs) [ 34 , 35 ]. Recently, we attempted to investigate the thermoelectric performance of BDT-based polymers with two-dimensional conjugated side-chains [ 36 ] and obtained good thermoelectric power factor of 101.3 μWm −1 K −2 , which is almost 100 times larger than that of the BDT–EDOT copolymers with one dimensional aliphatic side chain (0.9 μWm −1 K −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, one highly conjugated building block, thienylene-vinylene-thienylene or thienylenevinylene thiophene, linked via vinylene (bearing double-bond characteristic) between two thiophenes, which presented high charge-carrier mobility as result of the increased degree of coplanarity for the polymer backbone, was widely investigated and applied in organic thin-film transistors (OTFT) and selected as the main chain incorporated into the polymer backbone for solar cells [33,[77][78][79][80][81][82][83]. However, selecting thienylenevinylene thiophene as the conjugated side chain attached onto backbone was overlooked to some extent and there were some limited examples [61][62][63]. In 2014, Kang et al introduced an alkylthienylenevinylene thiophene (R-TVT) side group into BDT to construct BDTTVT and then copolymerized with dithienyl thieno[3,4-c]pyrrole-4,6-dione (DTTPD) to prepare PBDTTVT-DTTPD and found that the R-TVT side chain red-shifted the absorption peak, increased the absorption intensity, and slightly reduced bandgap, as well as creating a more advantaged microstructure of morphology, resulting in a 35.4% increased J SC and thus 25.3% improved PCE from 4.82% to 6.04%, respectively, compared to control polymer PBDTT-DTTPD bearing alkylthienyl side group onto BDT [61].…”
Section: Introductionmentioning
confidence: 99%
“…Following this, the alkyloxy side chain onto BDT in PTB7 was replaced with alkylthiothienylenevinylene thiophene (RS-TVT) to develop a 2D CP PBT-TVT, and a greatly improved absorption ranged from 300 to 550 nm, reduced optical band gap from 1.63 to 1.53 eV, 0.06 down-shifted E HOMO , more ordered solid film stacking, and 2.22-times raised µ h were observed, leading to synergistically increased V OC and J SC and corresponding 9.7% enhanced PCE from 7.41% to 8.13% as the result of prolonged conjugation of incorporating RS-TVT on BDT [62]. Recently, our group developed a 4,5-didecyl-thienylenevinylene thiophene (DR-TVT) modified BDT-containing CPs and investigated the effect of electron withdrawing [63]. As for the various electron-acceptor units utilized, benzo[c] [1,2,5]-thiadiazole (BT) and its derivatives were considered as the stronger electron-withdrawing moieties and tremendous BT-based semiconducting materials have been focused on, because of subtly integrating its electron accepting property and its ability to adopt the quinoid structure, easy availability, and modification [7,20,21,24,28,35,37,41,42,47,49,50,58,63,64,73,[84][85][86][87][88].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increasing degree of conjugation and hyperconjugation can reduce the energy gap of the liquid molecule, which is in agreement with the UV−vis experimental result in Figure 2a. 51,52 The massive excited electron transit from the valence band or trap level to the conduction band occurs after gaining sufficient energy during the electrical breakdown process. This is an effective way to investigate the electronic structure of a material using UV−vis spectroscopy.…”
mentioning
confidence: 99%
“…Therefore, the electrical breakdown field of BT is higher than that of PEPE, but the DB is the lowest. Furthermore, the increasing degree of conjugation and hyperconjugation can reduce the energy gap of the liquid molecule, which is in agreement with the UV−vis experimental result in Figure2a 51,52. The massive excited electron transit from the valence band or trap level to the conduction band occurs after gaining sufficient energy during the electrical breakdown process.…”
mentioning
confidence: 99%